Tax education and first category income tax collection in Peru vian university students - Callohuanca, Edgar (2020)
The objective was to evaluate the level of tax education related to the first category income tax collection in Peruvian university students. This work is in the quantitative approach, descriptive type, and cross-correlational design. The sample consisted of 3,560 students (between men and women between 18 and 25 years old), which was obtained using the non-probabilistic and convenience sampling technique. To obtain data, the Tax Education Questionnaire was applied, which was prepared by the authors under the theoretical assumptions of the Tax Court attached to the Ministry of Economy and Finance of Peru. The statistical processing was carried out using the variance analysis technique (ANOVA) of the variables tax education (1) and tax collection (2). The results indicated that there is a direct association between the mentioned variables with a p-value = 0.001. In conclusion, tax education is directly related to tax collection.